Pandangan Criminal Justice System Terhadap Peran Aparat Penegak Hukum Dalam Pencegahan Tindak Pidana Narkotika Di Dki Jakarta - Sahrul, Farhan Ananda; Firmansyah, Hery (LPPM STAI Muhammadiyah Probolinggo, 2025)
Narcotics are one of the most serious crimes faced by almost every country in the world, including Indonesia. In 2023, the number of drug users in Indonesia reached 3.3 million people, or approximately 1.73% of the total population. The province of DKI Jakarta was recorded as the most vulnerable area, contributing around 12.73% of the total narcoticsrelated crimes that year. This situation requires serious attention, particularly from law enforcement officers as part of the criminal justice system. Preventive actions taken by law enforcement should demonstrate effectiveness through a decrease in prevalence rates in 2024. This study uses a qualitative method through literature review by analyzing various sources such as journals, theses, and other scientific works. The approach used is normative, by examining the implementation of established legal principles. The results of this study show that law enforcement officers have taken several preventive measures to reduce narcotics use, including socialization, education, rehabilitation, and coaching for inmates. The coaching involves vocational training for convicts to prevent recidivism. However, the effectiveness of these efforts has yet to yield positive results, as the number of drug users in 2024 increased by 29.10%.